Metacognition Analysis of 7th Grade Students Junior High School After Applying Li-Pro-GP Learning Design - Yuni Pantiwati; Endrik Nurrohman; Ribut Suprihatin; Tasya Novian Indah Sari (Postgraduate, University of Mataram, 2023)
Students' metacognitive abilities develop from the knowledge they have and the management of that knowledge. Knowledge management will lead to students' strategies and skills in solving problems and higher-order thinking skills. The students' metacognitive skills play a major role in activities involving cognitive abilities such as understanding, communicating, paying attention, remembering, and solving problems. This research was aimed to find out the metacognitive skill of 7th grade students of Junior High School 23 Malang after applying Li-Pro-GP (literasi berbasis proyek terintegrasi GLS dan PPK: Li-Pro-GP) Learning Design. This is a descriptive qualitative research. It takes time from August to October 2021. This research was carried out at Junior High School 23 Malang. The population were 7th grade students and the sample were students of class VII.2 and VII.4. The research procedures included; 1) compiling MAI questionnaires to measure metacognitive ability in the form of short questions using likert scale (1-4), 2) giving students an instrument via Google Form before and after giving the Li-Pro-GP learning model. The instrument used to collect data was MAI (Metacognitive Awareness Inventory) from Schraw and Dennison. The method used to collect data is giving questionnaires to students. Data analysis technique was using Independent T test. The results of this study indicated that students' metacognitive abilities increased after the implementation of Li-Pro-GP learning model (sig 0.000 < 0.05). Apart from the research results obtained, further research can apply Li-Pro-GP model to teach other materials.